2018
DOI: 10.1016/j.btre.2018.e00263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dairy processing wastewater biotreatment in an IASBR system: Aeration rate impacts on performance and microbial ecology

Abstract: HighlightsDairy processing wastewater biotreatment using IASBR technology is proposed.Minor (0.2 LPM) aeration rate variations heavily influenced efficiency and ecology.Optimal nutrient removal efficiencies (≥92%) achieved under 0.6LPM aeration rate.Comamonadaceae stably enriched in reactor biomass (>80% relative abundance).Comamonadaceae top contributor of nitrogen and phosphorus assimilation genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…The high demand milk and milk products has led to an increase in dairy production globally. In the EU, since the removal of milk production quotas in 2015, the dairy industry has undergone rapid growth (Gil-Pulido et al, 2018). Dairy plants produce large volumes of wastewater; it is estimated that 1-2 m 3 of wastewater is produced per m 3 of manufactured milk (Quaiser and Bitter, 2016;Slavov, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high demand milk and milk products has led to an increase in dairy production globally. In the EU, since the removal of milk production quotas in 2015, the dairy industry has undergone rapid growth (Gil-Pulido et al, 2018). Dairy plants produce large volumes of wastewater; it is estimated that 1-2 m 3 of wastewater is produced per m 3 of manufactured milk (Quaiser and Bitter, 2016;Slavov, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dairy plants produce large volumes of wastewater; it is estimated that 1-2 m 3 of wastewater is produced per m 3 of manufactured milk (Quaiser and Bitter, 2016;Slavov, 2017). These wastewaters are characterized by high organic load and nutrient composition (Demirel et al, 2005;Lateef et al, 2013;Gil-Pulido et al, 2018). Several approaches, including physical-chemical and biological processes, are applied to treat dairy wastewaters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions of the dominant OTUs to the activity involved in the nitrogen and phosphate cycles in wastewater treatment systems, as defined by Gonzalez‐Martinez et al and Gil‐Pulido et al, are shown in Supporting Information Figure S2. With respect to nitrification genes, the autotrophic ammonia oxidation genes amo and hao were not found in any of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Many dominant OTUs appear to have the potential to contribute polyphosphate kinase capacities, which has been closely related to the phosphate biological removal . These were Otu0002, Otu0003, Otu0004, Otu0005, Otu0006, Otu0007, Otu0008, Otu0009, Otu0013, Otu0014, Otu0016, and Otu0022.…”
Section: Resultsmentioning
confidence: 99%